Ukraine's Orange Revolution - Wilson, Andrew, 1961- (Yale University Press, 2005)
"The remarkable popular protest in Kiev and across Ukraine following the cooked presidential election of November 2004 has transformed the politics of eastern Europe. Andrew Wilson here looks behind the headlines to ascertain what really happened and how it will affect the future of the region." "It is a dramatic story: an outgoing president implicated via secret tape-recordings in corruption and murder; a shadowy world of political cheats and manipulators; the massive covert involvement of Putin's Russia; the attempted poisoning of the opposition challenger; and finally the mass protest of half a million Ukrainians which forced a second poll and the victory of Viktor Yushchenko." "As well as giving an account of the election and its aftermath, the book examines the broader implications of the Orange Revolution and of Russia's serious miscalculation of its level of influence. It explores the likely chain reaction in Moldova, Belarus and the nervous autocracies of the Caucasus, and points to a historical transformation of the geopolitics of Eurasia. The book looks in close detail at the leaders of the Orange Revolution, and questions whether they can deliver the radical changes promised."--Jacket